Tetramisole is a new IK1 channel agonist and exerts IK1‐dependent cardioprotective effects in rats. Issue 4 (26th July 2022) - Liu, Qinghua; Sun, Jiaxing; Dong, Yangdou; Li, Pan; Wang, Jin; Wang, Yulan; Xu, Yanwu; Tian, Xinrui; Wu, Bowei; He, Peifeng; Yu, Qi; Lu, Xuechun; et al.
Abstract: Cardiac ischemia, hypoxia, arrhythmias, and heart failure share the common electrophysiological changes featured by the elevation of intracellular Ca 2+ (Ca 2+ overload) and inhibition of the inward rectifier potassium (IK1 ) channel. IK1 channel agonists have been considered a new type of anti‐arrhythmia and cardioprotective agents. We predicted using a drug repurposing strategy that tetramisole (Tet), a known anthelminthic agent, was a new IK1 channel agonist. The present study aimed to experimentally identify the above prediction and further demonstrate that Tet has cardioprotective effects. Results of the whole‐cell patch clamp technique showed that Tet at 1–100 μmol/L enhanced IK1 current, hyperpolarized resting potential (RP), and shortened action potential duration (APD) in isolated rat cardiomyocytes, while without effects on other ion channels or transporters. In adult Sprague–Dawley (SD) rats in vivo, Tet showed anti‐arrhythmia and anticardiac remodeling effects, respectively, in the coronary ligation‐induced myocardial infarction model and isoproterenol (Iso, i.p., 3 mg/kg/day, 10 days) infusion‐induced cardiac remodeling model. Tet also showed anticardiomyocyte remodeling effect in Iso (1 μmol/L) infused adult rat ventricular myocytes or cultured H9c2 (2‐1) cardiomyocytes. Tet at 0.54 mg/kg in vivo or 30 μmol/L in vitro showed promising protections on acute ischemic arrhythmias, myocardial hypertrophy, and fibrosis. Molecular docking was performed and identified the selective binding of Tet with Kir2.1. The cardioprotection of Tet was associated with the facilitation of IK1 channel forward trafficking, deactivation of PKA signaling, and inhibition of intracellular calcium overload. Enhancing IK1 may play dual roles in anti‐arrhythmia and antiventricular remodeling mediated by restoration of Ca 2+ homeostasis. Abstract :